The Islamic utopia the illusion of reform in Saudi Arabia - Hammond, Andrew 1970- (Pluto Press, 2012)
Will Saudi Arabia join the democratic wave in the Middle East? Despite being surrounded by states experiencing uprisings and revolutions, Saudi Arabia appears to be a "black hole" for democracy in the Middle East - secretive, highly repressive and still propped up by the West. The Islamic Utopia uses a range of sources including first-hand reporting and recently released WikiLeaks documents to examine Saudi Arabia in the decade after the 9/11 attacks, when King Abdullah's "reform" agenda took center state in public debate. It considers Saudi claims of "exemption" from the democratic demands of the Arab Spring. Andrew Hammond argues that for too long Western media and governments have accepted Saudi leaders' claims to be a buttress against Jihadist Islam and that a new policy is needed towards the House of Saud.